Dimensões do conteúdo gerado por usuário em videogames: cultura participativa e a intervenção criativa através do Modding - Capasso, Caio Assis (2014)
This research aims to verify how videogames allow the creation, sharing and collaboration of user-generated content, and the characteristics of fan communities that are created to such objective. For this work we minimally define videogames as digital games that are dependent of a computational support for its realization. Some useful videogames for the better understanding of the activities of creation and alteration of content by players and the manner they happen, particularly the creation of mods: the name commonly used to refer to the practice of alteration of a videogame s characteristics through the manipulation of files and/or processes that are constitute it, resulting in a different experience from the one originally planned by its developer. With this we try to offer clues and pointers towards a deeper understanding of the manners the roles of producer and consumer, author and user, player and fan are transforming with the ascension of new technologies and now (digital) media. With this intent we give special attention to the players turned modders amateur content creators for a specific videogame -, through the online communities engaged in the creation and distribution of this kind of content. Three author groupings are used as theoretical foundation for this research. The first é composed by authors that helps us to think questions regarding participatory culture and the promises of the internet, among them we can cite Howard Rheingold, Sherry Turkle, clary Shirky, Axel Bruns and particularly Mizuko Ito and Henry Jenkins. In the second grouping Katie Salen and Eric Zimmerman and Jesper Juul offer the concepts that allow us to take into account the expressive dimensions od videogames. The third grouping, with a special emphasis in the works of Olli Sotamaa, David Nieborg and Julian Kucklich that offers us empirical study cases for us to study the questions related to modding as a productive practice. We attempt to operationalize a theoretical perspective that deal with the expressive potential of videogames and how the interventions characterized as mods are one of the most intriguing ways to subvert the author/user and producer/consumer relationships. We also attempt to suggest similarities and differences between videogames and other media. Other objective is to enrich the debate regarding online participation and the artifacts it produces, trying to think participatory culture and the media convergence in the contemporary consumption and production practices through videogames